Navigated Transcranial Magnetic Stimulation (nTMS) based Preoperative Planning for Brain Tumor Treatment - Riaz, Hammad; Uzair, Mohammad; Arshad, Muhammad; Hamza, Ali; Bukhari, Nedal; Azam, Faisal; Bashir, Shahid (CNS & neurological disorders. Drug targets, 2024)
Transcranial Magnetic Stimulation (TMS) is a non-invasive technique for analyzing the central and peripheral nervous system. TMS could be a powerful therapeutic technique for neurological disorders. TMS has also shown potential in treating various neurophysiological complications, such as depression, anxiety, and obsessive-compulsive disorders, without pain and analgesics. Despite advancements in diagnosis and treatment, there has been an increase in the prevalence of brain cancer globally. For surgical planning, mapping brain tumors has proven challenging, particularly those localized in expressive regions. Preoperative brain tumor mapping may lower the possibility of postoperative morbidity in surrounding areas. A navigated TMS (nTMS) uses magnetic resonance imaging (MRI) to enable precise mapping during navigated brain stimulation. The resulting magnetic impulses can be precisely applied to the target spot in the cortical region by employing nTMS. This review focuses on nTMS for preoperative planning for brain cancer. This study reviews several studies on TMS and its subtypes in treating cancer and surgical planning. nTMS gives wider and improved dimensions of preoperative planning of the motor-eloquent areas in brain tumor patients. nTMS also predicts postoperative neurological deficits, which might be helpful in counseling patients. nTMS have the potential for finding possible abnormalities in the motor cortex areas.
Keywords: Magnetic Resonance Imaging; předoperační péče; neuronavigace; nádory mozku; Brain Mapping; magnetická rezonanční tomografie; Humans; Neuronavigation; Preoperative Care; motorické korové centrum; lidé; transkraniální magnetická stimulace; mapování mozku; Brain Neoplasms; Motor Cortex; Transcranial Magnetic Stimulation